2015
DOI: 10.1177/1403494815619256
|View full text |Cite
|
Sign up to set email alerts
|

The ethnic gap in mental health: A population-based study of Russian, Somali and Kurdish origin migrants in Finland

Abstract: Mental health symptoms are highly prevalent particularly in Kurdish migrants in Finland. Holistic interventions and co-operation between integration and mental health services are acutely needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 27 publications
(41 reference statements)
7
62
1
2
Order By: Relevance
“…Their lives have changed dramatically as they escaped from communities they have stayed all their lives and provided for themselves to where they had to rely on others. This finding is consistent with studies by Ager and Strand (2008), Hirani et al, (2015), Rask et al, (2016) and Wright et al, (2016) who reported that the change in environment of refugees, coupled with struggle for survival and adaptation, is one major source of stress. For instance, as reported by Reinelt et al, (2016) and Schick et al, (2016), such a turn-around is worse in the event where there is differences in culture between refugees and their new communities.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Their lives have changed dramatically as they escaped from communities they have stayed all their lives and provided for themselves to where they had to rely on others. This finding is consistent with studies by Ager and Strand (2008), Hirani et al, (2015), Rask et al, (2016) and Wright et al, (2016) who reported that the change in environment of refugees, coupled with struggle for survival and adaptation, is one major source of stress. For instance, as reported by Reinelt et al, (2016) and Schick et al, (2016), such a turn-around is worse in the event where there is differences in culture between refugees and their new communities.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Holmes et al, (2017) Joyce and Liamputtong (2017), stated that the western culture of individualism and independence makes it hard for refugees who find themselves in such environment to resettle and integrate with members of the community effectively. In some cases, they are seen as burden on public purse and competitors for limited economic opportunities and subjected to discrimination (Akua-Sakyiwa, 2017;Holmes et al, 2017;Rask et al, 2016). Their inability to socialise and see themselves as equal stakeholders in the society make it hard for them to overcome their losses and begin afresh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It includes 25 items on depressive and anxiety symptoms during the preceding week, rated on a scale from 1, ‘not at all bothered’ to 4, ‘extremely bothered’. Mean scores for the HSCL‐25 were calculated, and a cut‐off point of 1.75 was applied to create a dichotomized variable for clinically significant symptoms (no/yes), as previously used .…”
Section: Methodsmentioning
confidence: 99%